Age-Stage, Two-Sex Life Table and Functional Response of Amblyseius orientalis (Acari: Phytoseiidae) Feeding on Different Nutrient Sources - Keyu Pan; Tianrong Xin; Yibing Chen; Hongyan Wang; Kexin Wen; Yimeng Liu; Zhenzhen Li; Zhiwen Zou; Bin Xia (Insects, 2022)
Amblyseius orientalis Ehara is a predatory mite that belongs to the family Phytoseiidae. It is mainly found in Jiangxi, Shanghai, Guangdong, and other areas of China. Although A. orientalis is a dominant predatory mite species in China and is also important for agriculture and biological control, not many studies have investigated it. Thus, research on A. orientalis is necessary. However, its application in biological control is hindered by the absence of techniques for the mass rearing of A. orientalis in captivity. We conducted experiments to determine the growth, development, reproduction, and functional response of A. orientalis in this study by indoor single-head rearing at 25 ± 1 °C, 65 ± 5% relative humidity, and a photoperiod of a 16 h:8 h light/dark cycle under laboratory conditions. The results of the age stage, two-sex life table showed that the individuals in the pollen + yeast and pollen + yeast + sucrose groups had significantly higher oviposition period, fecundity, net reproductive rate (R0), and gross reproduction rate (GRR) than those in the pollen group. The results of the function response showed that the pollen + yeast + sucrose group was the most favorable for captive breeding of A. orientalis and had the best predatory ability along with rejuvenation and recovery ability. The results of the study provided a theoretical basis for indoor rearing, propagation, and utilization of A. orientalis.